The taste of Romanitas. Evidence of innovation in the culinary practice at Nora between the first century BC and the second century AD - Giannattasio, Bianca Maria; Pallecchi, Silvia (O T I V M, 2021)
Nora is a town with a long story and a complex cultural tradition that, in its first centuries, appears to be strictly linked to the customs and practices of the Punic world. This tradition, also facilitated by the geographic position on the Mediterranean Sea, can be easily found in the culinary practices, as proved by kitchenware and food preparation pottery shapes used between the 4th century BC and the 2nd century BC. As it happened in the construction of imposing buildings of the town, and also in the practices of everyday life, innovations coming from the Roman culture are progressive and particularly slow and the spread of the new tendencies lives together with the persistence of the Punic underlayers. Markers of these changes are visible in the private and public life, where the adoption of codified forms used for the self-representation is evident (for instance in buildings and in the tableware pottery). Other markers, certainly less obvious but as much as important and even more substantial, demonstrate the deep rootedness of some Roman habits, that merge with the local traditions, regardless of the exterior appearance of the self-representation. Amongst these last markers, there is the use of some pottery shapes, that clearly shows a change in the taste of preparing and cooking food.